2020
DOI: 10.3390/cells9030666
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid Virulence Factors of Mycobacterium tuberculosis Exert Multilayered Control over Autophagy-Related Pathways in Infected Human Macrophages

Abstract: Autophagy is an important innate immune defense mechanism that controls Mycobacterium tuberculosis (Mtb) growth inside macrophages. Autophagy machinery targets Mtb-containing phagosomes via xenophagy after damage to the phagosomal membrane due to the Type VII secretion system Esx-1 or via LC3-associated phagocytosis without phagosomal damage. Conversely, Mtb restricts autophagy-related pathways via the production of various bacterial protein factors. Although bacterial lipids are known to play strategic functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 67 publications
(119 reference statements)
1
33
0
Order By: Relevance
“…Consistent with this anti-inflammatory effect a PDIM-deficient Mm strain shows an increase in MyD88dependent recruitment of macrophages to the granuloma in the zebrafish model (Cambier et al, 2014). Their presence also stimulates Mtb phagocytosis mediated by CR3 (Astarie-Dequeker et al, 2009), contributes to the phagosome maturation inhibition (Astarie-Dequeker et al, 2009;Passemar et al, 2014), modulates autophagic response (Bah et al, 2020), is required for phagosomal escape and cell death induction (Augenstreich et al, 2017;Barczak et al, 2017;Quigley et al, 2017). Studies of infection of human endothelial cells also showed that PDIMs are required for phagosomal escape (Lerner et al, 2018) and intracellular cording (Lerner et al, 2020).…”
Section: Pdim Pglmentioning
confidence: 69%
See 1 more Smart Citation
“…Consistent with this anti-inflammatory effect a PDIM-deficient Mm strain shows an increase in MyD88dependent recruitment of macrophages to the granuloma in the zebrafish model (Cambier et al, 2014). Their presence also stimulates Mtb phagocytosis mediated by CR3 (Astarie-Dequeker et al, 2009), contributes to the phagosome maturation inhibition (Astarie-Dequeker et al, 2009;Passemar et al, 2014), modulates autophagic response (Bah et al, 2020), is required for phagosomal escape and cell death induction (Augenstreich et al, 2017;Barczak et al, 2017;Quigley et al, 2017). Studies of infection of human endothelial cells also showed that PDIMs are required for phagosomal escape (Lerner et al, 2018) and intracellular cording (Lerner et al, 2020).…”
Section: Pdim Pglmentioning
confidence: 69%
“…Purified and synthetic SL-1 has antagonistic binding activity to TLR-2 which mediates decreased NF-κB activation, reduced pro-inflammatory cytokine production and costimulatory molecule expression (Blanc et al, 2017). In the same fashion, a report found that SL can inhibit autophagy through MyD88 signaling (Bah et al, 2020). SL-1 have no effect on virulence of Mtb in the mouse and guinea pig model (Rousseau et al, 2003b;Chesne-Seck et al, 2008).…”
Section: Tdm Dat/pat Sl-1mentioning
confidence: 97%
“…This is the case for Man-Lam, TDM, PIM and PDIM, which, besides their role in phagocytosis, also mediate intracellular trafficking and vacuole maturation arrest induced by M. tuberculosis (Passemar et al, 2014). More recently, PDIM and SL were shown to be involved in controlling autophagy-related pathways in human macrophages (Bah et al, 2020). tuberculosis and ancestral species revealed a restructuring of the mycomembrane glycolipid components, including mycolic acids and free lipids of the outer leaflet (Dulberger et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…This is the case for Man-Lam, TDM, PIM, and PDIM, which, besides their role in phagocytosis, also mediate intracellular trafficking and vacuole maturation arrest induced by M. tuberculosis (Passemar et al, 2014). More recently, PDIM and SL were shown to be involved in controlling autophagy-related pathways in human macrophages (Bah et al, 2020). Considering the changes observed in the PDIM content of the MtbΔfasR mutant, we analyzed the acidification of phagosome during infection of human macrophages.…”
Section: Discussionmentioning
confidence: 99%